Spillover effects of HIV testing policies: changes in HIV testing guidelines and HCV testing practices in drug treatment programs in the United States - Frimpong, Jemima A. (BMC Public Health, 2016)
BACKGROUND: To examine the extent to which state adoption of the Centers for Disease Control and Prevention (CDC) 2006 revisions to adult and adolescent HIV testing guidelines is associated with availability of other important prevention and medical services. We hypothesized that in states where the pretest counseling requirement for HIV testing was dropped from state legislation, substance use disorder treatment programs would have higher availability of HCV testing services than in states that had maintained this requirement. METHODS: We analyzed a nationally representative sample of 383 opioid treatment programs from the 2005 and 2011 National Drug Abuse Treatment System Survey (NDATSS). Data were collected from program directors and clinical supervisors through telephone surveys. Multivariate logistic regression models were used to measure associations between state adoption of CDC recommended guidelines for HIV pretest counseling and availability of HCV testing services. RESULTS: The effects of HIV testing legislative changes on HCV testing practices varied by type of opioid treatment program. In states that had removed the requirement for HIV pretest counseling, buprenorphine-only programs were more likely to offer HCV testing to their patients. The positive spillover effect of HIV pretest counseling policies, however, did not extend to methadone programs and did not translate into increased availability of on-site HCV testing in either program type. CONCLUSIONS: Our findings highlight potential positive spillover effects of HIV testing policies on HCV testing practices. They also suggest that maximizing the benefits of HIV policies may require other initiatives, including resources and programmatic efforts that support systematic integration with other services and effective implementation.